A Role of the Professional Competency Perception as a Significant Predicting Factor for Self-Perceived Person-Job Fit and Misfit of Doctor of Pharmacy Graduates in Thailand - คำไชยเทพ นิจนาวี; สุนันทิวัฒน์ มนทยา; ไมตรีมิตร ผกามาศ; อนุรัตน์พานิช ลือรัตน์ (Journal of Health Science of Thailand, 2021)
The six-year Doctor of Pharmacy program (Pharm D) was mandated in Thailand with the expectation to produce specialty pharmacists who were advance in pharmacy competency and meet the demands of the current job market. However, the Doctor of Pharmacy graduates’ suitability to the job has never been evaluated in the big picture. This study aimed to investigate person-job fit and misfit among Pharm D graduates and identify factors affecting person-job fit and misfit. The cross-sectional survey was conducted using an internet-based self-administrated questionnaire for data collection. There were 163 responses included in the study. The person-job fits were determined in two dimensions, the expected person-job fit and the self-perceived person-job fit. The data analysis showed that over two-thirds (79%) of pharmacy graduates were female. Age ranged from 24 to 44 years, with the age median at 26 years. The majority of the Pharm D graduates were graduated in the pharmaceutical care program from the government university. Among this, about 80% of respondents were working in pharmaceutical care positions, and 20% in the industrial pharmacy position. The graduates perceived their professional competency as competent (74% in both pharmaceutical care and industrial pharmacy) and a very competent level (17% in pharmaceutical care and 15% in the industrial pharmacy). There were 58% of Pharm D graduates perceived they had a person-job fit. The distribution of self-perceived person-job fit and misfit was not different across the programs. This study directly represented the graduates’ viewpoint on their compatibility in real-world practice. The high percentage of a self-perceived person-job misfit should not be overlooked. The graduates from both programs expressed the same level of the feeling that they were not fit to the job even though their perception toward pharmacy professional competency is competent. Future research should be conducted to obtain more information regarding the misfit phenomenal as well as to understand how the perceived fit and misfit occurred.